Contribuições freudianas acerca do antagonismo entre atividade e passividade no desenvolvimento psicossexual: da fantasia infantil ao encontro da realidade adolescente - Santos, Fernanda Digieri dos (Universidade Federal de São Carlos, 2025)
Freud's work is marked by dualism, being the antagonism between activity and passivity highlighted as the precursor of the sexual polarity that runs through the psyche. Passivity is predominant in childhood, considering that the infant experiences helplessness since the moment of birth, and although they progressively conquer greater autonomy over their own body, their capacity for action in reality is limited to the possibilities made available by the ones that care for them. This passivity, however, is not absolute, because the child elaborates the renunciation of their drives by relying on fantasy, as demonstrated in the game of the reel, reported by Freud in 1920. Puberty, however, marks the beginning of what we now call adolescence, and brings with it several transformations in the psychosexual dynamics. These changes involve the detachment of family authority, the confrontation with the facts of sex and an urgency to move to the act in the sphere of reality, with fantasy being no longer sufficient to placate one’s anxieties. Thus, the present work intended to describe the theoretical subsidies in Freud's work that allows adolescence to be described as a transitory psychic period in relation to the activity-passivity antagonism, marking the abandonment of infantile passivity as the pubescent begins to conquer autonomy over their own body and surrounding world. To this end, an analysis of Freud's work was carried out from a reading of the articulation, delineations and projections that Freud's discourse proposes, based on Monzani’s Philosophy of Psychoanalysis.
Freudian contributions to the antagonism between activity and passivity in psychosexual development: from childhood fantasy to the reality of adolescence
Keywords: Desenvolvimento psicossexual; Atividade-passividade; Fantasia; Puberdade; Psychosexual development; Activity-passivity; Fantasy; Puberty; CIENCIAS HUMANAS::FILOSOFIA::EPISTEMOLOGIA